Analysis of the genotoxic potential of low concentrations of Malathion on the Allium cepa cells and rat hepatoma tissue culture - Bianchi, Jaqueline [UNESP]; Mantovani, Mario Sérgio; Marin-Morales, Maria Aparecida [UNESP] (Elsevier B. V., 2015)
Based on the concentration of Malathion used in the field, we evaluated the genotoxic potential of low concentrations of this insecticide on meristematic and F1 cells of Allium cepa and on rat hepatoma tissue culture (HTC cells). In the A. cepa, chromosomal aberrations (CAs), micronuclei (MN), and mitotic index (MI) were evaluated by exposing the cells at 1.5, 0.75, 0.37, and 0.18mg/mL of Malathion for 24 and 48hr of exposure and 48hr of recovery time. The results showed that all concentrations were genotoxic to A. cepa cells. However, the analysis of the MI has showed non-relevant effects. Chromosomal bridges were the CA more frequently induced, indicating the clastogenic action of Malathion. After the recovery period, the higher concentrations continued to induce genotoxic effects, unlike the observed for the lowest concentrations tested. In HTC cells, the genotoxicity of Malathion was evaluated by the MN test and the comet assay by exposing the cells at 0.09, 0.009, and 0.0009mg/5mL culture medium, for 24hr of exposure. In the comet assay, all the concentrations induced genotoxicity in the HTC cells. In the MN test, no significant induction of MN was observed. The genotoxicity induced by the low concentrations of Malathion presented in this work highlights the importance of studying the effects of low concentrations of this pesticide and demonstrates the efficiency of these two test systems for the detection of genetic damage promoted by Malathion.
Keywords: Chromosomal aberration; Comet assay; Htc; Micronuclei; Pesticide